REKAYASA PROSES SINTESIS PIPERONAL DARI KULIT LAWANG (Cinnamomum culilawan Blume) SEBAGAI PREKURSOR OBAT KANKER - Imanuel Berly Delvis Kapelle; Tun Tedja Irawadi; Meika Syahbana Rusli; Djumali Mangunwidjaja; Zainal Alim Mas'ud (Jurnal Penelitian Hasil Hutan, 2016)
Piperonal as a precursor of cancer drug (Curcumin analogues) can be synthesized from extract of lawang’s bark (Cinnamomum culilawan Blume) with multiple stages, among others: isolation of  essential oils, isolation safrole, safrole isomerization, and synthesis of piperonal. Essential oils were isolated from the bark of lawang (the water content of 46.2%) using a water distillation system with 1/3 volume of high boiler for five hours. Isolation of safrole from lawang bark oils was performed using NaOH solution and purified using reduced pressure distillation system at a temperature of 90-123°C / 1 mmHg. The safrole isomerization was undergone using alkali catalyst (KOH) without solvent at a temperature of 120°C for 8 hours. Oxidation of isosafrol was performed using KMnO4 in acidic conditions using a KTF tween 80 at a temperature below 30°C, and purified using silica gel. Results of isolation yield 0.94% with 14 components were determined through GC-MS, including 67.35% eugenol, safrole 13.96%, 12.61% methyl eugenol, 4-terpineol sineol 1.79% and 1.55%. The isolated safrole yield of 17.21% with purity testing and identification using FTIR, 1H- NMR and GCMS confirmed the product was safrole. The isomerization obtained yield of 77.56% with GC analysis indicated compounds of  cis-isosafrole and trans-isosafrole. The results of  oxidation obtained yield of  65.63% with a purity of 100% by GCMS and the 1H-NMR indicated the product is piperonal.